2014
DOI: 10.1021/ac500281r
|View full text |Cite
|
Sign up to set email alerts
|

A Polymeric Liquid Membrane Electrode Responsive to 3,3′,5,5′-Tetramethylbenzidine Oxidation for Sensitive Peroxidase/Peroxidase Mimetic-Based Potentiometric Biosensing

Abstract: The oxidation of 3,3′,5,5′-tetramethylbenzidine (TMB) has great utility in bioanalysis such as peroxidase/ peroxidase mimetic-based biosensing. In this paper, the behaviors of TMB oxidation intermediates/products in liquid/liquid biphasic systems have been investigated for the first time. The free radical, charge transfer complex, and diimine species generated by TMB oxidation are all positively charged under acidic and near-neutral conditions. Electron paramagnetic resonance and visible absorbance spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 66 publications
0
33
0
Order By: Relevance
“…Qin's group found that the G-quadruplex/hemin DNAzyme-catalyzed oxidative coupling of monomeric phenols can induce large potential signals on quaternary ammonium salt-doped polymeric membrane electrodes. Two label-free potentiometric DNA assay protocols based on the Gquadruplex/hemin DNAzyme have been developed with sensitivities higher than those of colorimetric and fluorometric method [101,102].…”
Section: Dna and Micrornamentioning
confidence: 99%
“…Qin's group found that the G-quadruplex/hemin DNAzyme-catalyzed oxidative coupling of monomeric phenols can induce large potential signals on quaternary ammonium salt-doped polymeric membrane electrodes. Two label-free potentiometric DNA assay protocols based on the Gquadruplex/hemin DNAzyme have been developed with sensitivities higher than those of colorimetric and fluorometric method [101,102].…”
Section: Dna and Micrornamentioning
confidence: 99%
“…Water was present in each solution in 50 v/v% by solubility determination of sodium salt of HEPES. The calibration solutions were prepared in 25 cm 3 flasks by placing 12.5 cm 3 of acetonitrile and then the necessary volumes of aqueous stock solution of solute were added. Finally the flasks were filled to the mark with water.…”
Section: Determination Of the Solubilities Of Hepes And Its Sodium Samentioning
confidence: 99%
“…This buffer was used in a vast number of studies. In many intra-and extracellular electrochemical studies it served as an appropriate choice [1][2][3][4] and in protein based detection applications [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, pH and ionic strength in biofluids can vary significantly and consequently result in important variations in the response and increase the background noise of the biosensors 32 . This is why, various research groups have tried to develop nanotechnologies to decrease the sizes of electrochemical sensor elements in order to increase the signal-to-noise ratio for the processes that occur at the interface of the device 33,34,35 . As a consequence, it is also possible to develop antibody molecules labeled with several molecules of the same enzyme to increase the signal resulting from the binding of one molecule to its target 32 .…”
Section: Limitations Inherent To Electrochemical Biosensorsmentioning
confidence: 99%